Responses of garlic to zinc, copper, boron and molybdenum Application in grey terrace soil of amnura soil series (Bangladesh Journal of Agricultural Research, 2016)
A field experiment was conducted at the Spices Research Centre, Shibgonj, Bogra, Bangladesh during rabi (winter) seasons of 2008-09 and 2009-10 to determine the requirement of Zn, Cu, B and Mo of garlic (BARI Garlic 2) along with a blanket dose of cowdung 5 t, 100 kg N, 40 kg P, 100 kg K and 30 kg S/ha for achieving satisfactory bulb yield of this crop. Different levels of zinc (0, 1.0, 1.5, 3.0 and 4.5 kg/ha), copper (0, 0.5, 1.0 and 1.5 kg/ha), boron (0, 1.0, 2.0 and 3.0 kg/ha) and molybdenum (0, 0.5 and 1.0 kg/ha) were distributed in the plot. The experiment was tested in randomized complete block design with three replications. The positive impact of application of those nutrients plant height, number of leaves per plant, cloves per bulb, diameter and weight of bulb and yield of garlic up to a moderate level of Zn3.0Cu1.0B3.0Mo1.0 kg/ha. The highest bulb yield (4.87 t/ha in 2008-09 and 6.6 t/ha in 2009-10) was obtained from Zn3.0Cu1.0B3.0Mo1.0 kg/ha and yield was declined with higher dose of these elements except Mo. The fertilizer treatment Zn3.0Cu1.0B3.0Mo1.0 kg/ha was observed to be the best suitable dose for garlic production on Grey Terrace Soil of Amnura Soil Series under AEZ-25 (Level Barind Tract) of Bangladesh.Bangladesh J. Agril. Res. 41(1): 85-90, March 2016